2021
DOI: 10.3389/fphys.2021.637480
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Sustains “Inflamed” Memory of Peripheral Immune Cells Aggravating Kidney Inflammatory Response in Chronic Kidney Disease

Abstract: The incidence of chronic kidney disease (CKD) has rapidly increased in the past decades. A progressive loss of kidney function characterizes a part of CKD even with intensive supportive treatment. Irrespective of its etiology, CKD progression is generally accompanied with the development of chronic kidney inflammation that is pathologically featured by the low-grade but chronic activation of recruited immune cells. Cumulative evidence support that aberrant DNA methylation pattern of diverse peripheral immune c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 111 publications
0
11
0
Order By: Relevance
“…The results of studies point out chronic inflammation as a factor implicated in the pathogenesis of various diseases, including CKD [21,22]. Inflammation also contributes to the progression of this disease [23]. The finding of diffuse interstitial infiltration of neutrophils, T lymphocytes, B lymphocytes, and monocytes within the kidney seems to confirm the importance of the aforementioned process.…”
Section: Chronic Kidney Diseasementioning
confidence: 88%
See 3 more Smart Citations
“…The results of studies point out chronic inflammation as a factor implicated in the pathogenesis of various diseases, including CKD [21,22]. Inflammation also contributes to the progression of this disease [23]. The finding of diffuse interstitial infiltration of neutrophils, T lymphocytes, B lymphocytes, and monocytes within the kidney seems to confirm the importance of the aforementioned process.…”
Section: Chronic Kidney Diseasementioning
confidence: 88%
“…The biological mechanisms related to CKD and its progression remain elusive [7]. Currently, the treatment of chronic kidney disease involves the management of common abnormalities, including proteinuria, hyperglycemia, hypertension, etc., however, in some patients these measures are not sufficient and thus they progress to end-stage renal disease (ESRD) [23]. Genome-wide association studies (GWAS) and epigenome-wide association studies (EWAS) have identified frequent variants within more than >400 genetic loci that are associated with renal function and the development of CKD [27][28][29][30].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…In this context, T cell dysregulation due to prolonged exposure of exogenous pathogens promotes the pro-inflammatory phenotype of multiple effector cells, which migrate into the involved kidneys remote from the original infection site and contribute to persistent inflammatory tissue injury (24,25). Importantly, the "inflamed" phenotype of peripheral T cells might sustain for a long time and affect the tissue inflammatory homeostasis after they migrate from the circulation into the involved kidney (26). Therefore, physicians need to comprehensively assess the clinical significance of T cell-mediated crosstalk among immune cells and consider the therapeutic potentials of targeting T cell activity in CKD progression with a timing-specific manner.…”
Section: The Rationale Of Targeting T Cell Dysregulation In Chronic Kidney Inflammation Upon Infectionmentioning
confidence: 99%